(untitled) (Communicare: Journal for Communication Studies in Africa, 2022)
Prior research suggests there is a lack of editorial-level policy thinking around HIV/AIDScoverage in South African media institutions. At the same time, constraints of time,capacity and resources, common in the commercial newsroom, mean it is often illequippedto deal more comprehensively with the complex effects of the pandemic in thecountry. A quantitative study, conducted as a sister study to this, shows the press tooka strongly critical position in relation to the government health policy on anti-retrovirals(ARVs) during the monitored periods (March-May 2002 and March-May 2003). Given therelative complexity of a public ARV treatment programme, the lack of resources andcapacity in the newsroom, as well as the lack of widespread editorial-level policy thinkingon HIV/AIDS coverage, how is it that the press came to represent a position so stronglyin opposition to the government policy? In the context of an overview of the quantitativefindings, this paper explores several possible reasons that emerged during interviewsconducted with key informants in the field of HIV/AIDS and the media.